Analysis of Translation Methods for Artistic Translation - Zаfаrjon, Djаlolov (PT. Antis International Publisher, 2024)
The main feature of artistic translation comes from the artistic function of the language. Language becomes an aesthetic phenomenon, an art fact in a work of art. The language of a literary work is the element of